Deployment and evaluation of an NH4+∕ H3O+ reagent ion switching chemical ionization mass spectrometer for the detection of reduced and oxygenated gas-phase organic compounds - C. L. Zang; M. D. Willis (Atmospheric Measurement Techniques)
Reactive organic carbon (ROC) is diverse in its speciation, functionalization, and volatility, with varying implications for ozone production and secondary organic aerosol formation and growth. Chemical ionization mass spectrometry (CIMS) approaches can provide in situ ROC observations, and the CIMS reagent ion controls the detectable ROC species. To expand the range of detectable ROC, we describe a method for switching between the reagent ions <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="3226c502fdca30fe88bf9305df4b3716"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00004.svg" width="24pt" height="15pt" src="amt-18-17-2025-ie00004.png"/></svg:svg> and H3O+ in a Vocus chemical ionization time-of-flight mass spectrometer (Vocus-CI-ToFMS). We describe optimization of ion–molecule reactor conditions for both reagent ions, at the same temperature, and compare the ability of <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="9641cdd414b305565815b5b604dabf23"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00005.svg" width="24pt" height="15pt" src="amt-18-17-2025-ie00005.png"/></svg:svg> and H3O+ to detect a variety of volatile organic compounds (VOCs) and semi-volatile and intermediate-volatility organic compounds (SVOCs and IVOCs), including oxygenates and organic sulfur compounds. Sensitivities are comparable to other similar instruments (up to ∼5 counts s−1 <msubsup>pptv-1</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="27pt" height="16pt" class="svg-formula" dspmath="mathimg" md5hash="03e69d0b8a5da11c6fbc4c8c60f3b361"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00006.svg" width="27pt" height="16pt" src="amt-18-17-2025-ie00006.png"/></svg:svg>), with detection limits on the order of 1–10 s of pptv (1 s integration time). We report a method for characterizing and filtering periods of hysteresis following each reagent ion switch and compare use of reagent ions, persistent ambient ions, and a deuterated internal standard for diagnosing this hysteresis. We deploy <msubsup>NH4+</msubsup>/H3O+<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="57pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="76eebc6c86e1f2961d607ea8607c9e30"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00007.svg" width="57pt" height="15pt" src="amt-18-17-2025-ie00007.png"/></svg:svg> reagent ion switching in a rural pine forest in central Colorado, US, and use our ambient measurements to compare the capabilities of <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="7b888eb222795ca6a6dd2ceb535b59a0"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00008.svg" width="24pt" height="15pt" src="amt-18-17-2025-ie00008.png"/></svg:svg> and H3O+ in the same instrument, without interferences from variation in instrument and inlet designs. We find that H3O+ optimally detects reduced ROC species with high volatility, while <msubsup>NH4+</msubsup><svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="24pt" height="15pt" class="svg-formula" dspmath="mathimg" md5hash="fc7f721ac75f3b099ec2891c91941f4b"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="amt-18-17-2025-ie00009.svg" width="24pt" height="15pt" src="amt-18-17-2025-ie00009.png"/></svg:svg> improves detection of functionalized ROC compounds, including organic nitrates and oxygenated SVOCs and IVOCs that are readily fragmented by H3O+.